2019
DOI: 10.4143/crt.2018.060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Estradiol in an Azoxymethane/Dextran Sulfate Sodium-Treated Mouse Model of Colorectal Cancer: Implication for Sex Difference in Colorectal Cancer Development

Abstract: The data suggest that estradiol inhibits the initiation of CRC by regulating Nrf2-related pathways. Moreover, these imply the dual role of Nrf2 and NLRP3 inflammasome, including promotion of tumor progression upon tumor initiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 28 publications
4
57
0
Order By: Relevance
“…These changes are characterized by increased proinflammatory macrophages infiltration and epithelia permeability in the colon, which eventually can lead to insulin resistance (7). Estrogen treatment has been shown to elicit an anti-inflammatory response in the colon of mouse models for colitis (28,46). Our transcriptomic data revealed that while both sexes showed altered immune response upon HFD feeding, there were sex differences in the immune response.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These changes are characterized by increased proinflammatory macrophages infiltration and epithelia permeability in the colon, which eventually can lead to insulin resistance (7). Estrogen treatment has been shown to elicit an anti-inflammatory response in the colon of mouse models for colitis (28,46). Our transcriptomic data revealed that while both sexes showed altered immune response upon HFD feeding, there were sex differences in the immune response.…”
Section: Discussionmentioning
confidence: 80%
“…Most of the CRC protective effect, however, has been linked to ERβ. Treatment with ERβ-selective agonist, for example, resulted in anti-inflammatory and anti-tumorigenic effects in different CRC mouse models (27)(28)(29)(30), and loss of ERβ results in pro-inflammatory environment and increased tumor development in both APC Min/+ and colitis-associated tumor mouse model (31,32)(Hases et al, under review). Notably, intestinal-specific deletion of ERβ strongly enhanced inflammatory signaling in the colon of both male and female mice (Hases et al, under review).…”
Section: Introductionmentioning
confidence: 99%
“…Most prominent are the corticosteroids, which are used to treat the acute relapse of inflammatory bowel disease (24, 25), and the macrolide antibiotics, which we have investigated further in this manuscript. Intriguingly the analysis also identified sex hormones such as medroxyprogesterone and estradiol which have been shown to modulate coli (26)tis, and colitis associated adnoma development in vivo (27); and non-steroidal anti-inflammatory drugs, which, in clinical practice, are identified as agents that exacerbate IBD (28). However, NSAIDs non-selectively inhibit cyclooxygenase (COX) activity resulting in inhibition of constitutively expressed COX-1 in the gastrointestinal epithelium, causing epithelial damage and ulceration; and inhibition of COX-2, which is upregulated at sites of inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…Our list of drugs predicted to influence IBD outcomes included several drugs in routine use for IBD, most prominently the corticosteroids, which are used to treat acute relapses of inflammatory bowel disease 24 25 . The analysis also identified sex hormones including medroxyprogesterone and estradiol which have been shown to modulate colitis 26 , and colitis-associated adenoma development in vivo 27 ; and non-steroidal anti-inflammatory drugs, which, in clinical practice, are identified as agents that exacerbate IBD 28 . The harmful effects of NSAIDs result from inhibition of constitutively expressed COX-1 in the gastrointestinal epithelium, causing epithelial damage and ulceration; inhibition of COX-2, which is upregulated at sites of inflammation is a well-established anti-inflammatory mechanism, which influences NF-κB signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, neural-immune-endocrine network including nerve growth factors has attracted increasing attention not only in IBS, 11 but also in esophageal 20,23,24 and gastric pathophysiology. 25 In the esophagus, TRPV1 receptors and neurotropic factors have been reported to play an important role in the inflammatory process. 23,24 Our team has also demonstrated that TRPV1, GDNF, and NGF are up-regulated in reflux esophagitis.…”
Section: Discussionmentioning
confidence: 99%